SOCIAL ACCOUNTING ASPECTS IN THE PREUNIVERSITY LEVEL REIMBURSEMENT OF STUDENTS - CENAR IULIANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2016)
The specific accounting approaches in preuniversity accounting are reduced, including the segment accounted for the reimbursementof students travel expenses and other benefits. This paper aims to outline an image of the social aspects of education in the preuniversity public education, represented by reimbursement to the beneficiaries of education, how they are reflected in accounting through the budget classification and disclosed to users via public media. Specifically, our approach refers to scholarships provided by the local administration to support learning, professionalscholarships, as well as various support programs for students who come from families with material difficulties, whose financial backer is the state through school inspectorates.